Effects of particle size on semicoke and high-volatile bituminous coal cofiring in reducing-to-oxidizing environment. (15th April 2022) - Yan, Yonghong; Zhu, Wenkun; Sun, Rui; Sun, Liutao; Chen, Dengke; Qi, Hongliang; Wu, Jiangquan
Highlights: Ignition distance of the same trend was obtained by multiple methods. Ignition transformed from homogeneous-heterogeneous to homogeneous mode at particle size of R90 = 25%. The ignition share of semicoke decreased with increasing particle size. Strong reducing zone was crucial to low NO emission for finer particle sized fuel stream. Abstract: The characteristics of semicoke and high-volatile bituminous coal comprising different-sized particles were experimentally studied during co-firing in a 300-kW pilot-scale down-fired furnace. Ignition was investigated in detail in the near-burner region wherein ignition transitioned from reducing to an oxidizing atmosphere similar to that in pulverized coal (pc) furnaces. Combustion characteristics—including ignition distance and mode, NO emission, and char burnout—were evaluated based on chemiluminescence spectra, flame temperature, and flue gas species. The results showed that the chemiluminescence-spectra measured ignition distance decreased with increasing particle size, which was consistent with the trends determined using gas temperature and flue-gas species analyses. An attempt was made to distinguish the relative contributions of semicoke and bituminous coal to the initiation ignition. The ignition mode transformed from nonhomogeneous to homogeneous at particle size of R90 = 25% because the semicoke ignition share was reduced in the blended fuel. A method was proposed for determining the intensive combustion zone and strong reducing zones ( S C and S R, respectively). The S C and S R areas both decreased with increasing particle size. The correlation between S R and the fuel-N/NO conversion ratio showed that a larger S R is the key to low NO emission. Because bituminous coal promoted semicoke ignition, stabler combustion and lower downstream NO emission, R90 ≤ 20% particles may be suitable for cofiring semicoke and bituminous coal.